Could Physical Activity Improve Healthy Lifestyles and Psychological Well-being? - González, Alfonso J. García (Advances in Social Sciences Research Journal, 2014)
It is clear the role that physical activity plays in psychological well-being and health. The main aim in this paper is evaluate the influence of the practice of regular physical activity in the adoption of healthy lifestyles and psychological well-being, in a sample of 183 students of the University of the Algarve, 94 regular physical activity practitioners and 89 who don´t. For the collection of data was applied a battery of instruments consisting of a Demographic Questionnaire and Physical Activity; by the Lifestyle Questionnaire (Carvalho & Cruz, 2006) and the Ryff’s Scales of Psychological Well-being (Fernandes, 2007). Our results show that the subjects who practice regular physical activity adopt healthier lifestyles, as well as provide superior results in environmental mastery dimension in the psychological well-being. The analysis of the interaction between the values of the lifestyle, organized into three levels, and the psychological well-being, reveals that participants with higher scores present superior rates of psychological well-being, globally and in dimensions (environmental mastery, purpose in life and self-acceptance).